COMPARISON OF CATCHING CRABS (Scylla sp) WITH MEAT AND CHICKEN BAITS USING PENTO FISHING GEAR IN SEA OF BATUBARA NORTH SUMATERA PROVINCE - Alman Aloisius Sirait; Arthur Brown; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was do in Decembre 2017 atTanjung Tiram village, Tanjung Tiram Subistrict, Batubara District, Nort Sumatera Province. The study aims to find effective feed and produce more catches using pento fishing gear. The research method used is the experimental method that is the comparison of the catch of crabs using bait fish and chicken on pento fishing gear in sea of Batubara. Repeating 10 times with 4 treatments. In one day was doing 2 times catches, setting start at high tide around 14.00 to 15.00 WIB, and hauling around 18.00 until 18.30 WIB. The results showed the most total catch with 15 chicken head bait and at least 8 stingray bait. And based on the weight is chicken head bait 2280 grams and lowest stingray bait 1230 grams. Based on the ANAVA test results for the number of catches, there was no effect of bait on the number of crab catches different from weight, there was effect of bait on the weight of crab catch. So that further tests Student Newman Keuls (SNK), which proves that there is no effect of the bait on the catch by either number or weight of crab catches. Then H0 is accepted and H1 is rejected.Key word: Pento Fishing Gear, Batubara, Crabs (Scylla sp), Baits